2010
DOI: 10.5012/bkcs.2010.31.6.1555
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Toxicity and Gene Expression Changes Triggered by Quantum Dots

Abstract: Quantum dots (QDs) are extensively employed for biomedical research as a fluorescence reporter and their use for various labeling applications will continue to increase as they are preferred over conventional labeling methods for various reasons. However, concerns have been raised over the toxicity of these particles in the biological system. Till date no thorough investigation has been carried out to identify the molecular signatures of QD mediated toxicity. In this study we evaluated the toxicity of CdSe, Cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…The expression of metallothionein superfamily genes were induced when treated with red and green QDs, however, these genes were not affected in blue QD treated samples. Metallothioneins (MTX2a, MTX1h, MTX1g, MTX1f) are metal binding proteins that play a role in detoxification and protect against ROS and are also upregulated when exposed to Cd 2+ ions [ 39 ].…”
Section: Quantum Dotsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of metallothionein superfamily genes were induced when treated with red and green QDs, however, these genes were not affected in blue QD treated samples. Metallothioneins (MTX2a, MTX1h, MTX1g, MTX1f) are metal binding proteins that play a role in detoxification and protect against ROS and are also upregulated when exposed to Cd 2+ ions [ 39 ].…”
Section: Quantum Dotsmentioning
confidence: 99%
“…Dua et al and coworkers found with microarray analysis that QD exposure induces the expression of genes involved in oxidative stress, apoptosis, and inflammation, which result in decreased cellular viability. Furthermore, they stated that QD-mediated toxicity is highly dependent on the core material (CdSe) and the coating (ZnS) partially reduces the toxic effects [ 39 ]. Their results suggest that the use of unmodified QDs in biomedical applications should be used carefully and with much consideration.…”
Section: Quantum Dotsmentioning
confidence: 99%
“…The lncRNA co-expressed DEGs in ESCC-associated gene set were screened out for GO terms as well as KEGG pathways enrichment analysis performed by Metascape, and construction of PPI network also using STRING and visualized by Cytoscape. The terms and pathways with the thresholds were set at a P<0.05 and the numbers of enriched genes ≥ 2 [22] were considered as significant to product bubble diagrams. The former five pivotal nodes in the PPI network with degree≥16 were identified to further analysis.…”
Section: Co-expression Analysis Of Selected Lncrnas With Degsmentioning
confidence: 99%
“…Numerous studies demonstrated that Cd ions can be released from QDs, which is poisonous for cells, in biological environments. 94,95 Cd ions can disrupt DNA replication and induce reactive oxygen species (ROS). 96,97 Through surface coating some functional molecules, the toxicity of QDs can be reduced, but it cannot thoroughly eliminate the potential toxicity.…”
Section: Intrinsic Drawbacks Of Qds Ucnps and Cds In Cancer Detectionsmentioning
confidence: 99%